2001
DOI: 10.1292/jvms.63.1245
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin Treatment of Demodicosis in 56 Hamsters.

Abstract: ABSTRACT. Fifty-six hamsters with demodicosis were treated with daily oral administration of ivermectin (0.3 mg/kg). Thirty-three cases (58.9%) were cured and 6 cases (10.7%) had improved clinically but needed to continue treatment. Of 5 cases (8.9%) who relapsed within 3 months and were retreated with ivermectin, 4 were cured and 1 needed further treatment. Five cases (8.9%) had improved clinically but died within 3 months. Seven cases (12.5%) had not improved and died within 3 months. Overall 49 (87.5%) hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The more commonly encountered neoplasms in these 2 species include epithelial papilloma, androgen‐dependent atypical fibroma, mammary gland adenoma, and plasmactyoma . Atypical fibroma (and its malignant variant, atypical fibrosarcoma) has rarely been reported in hamsters and, to the best of the authors' knowledge, has never been reported in a Roborovski hamster.…”
Section: Discussionmentioning
confidence: 99%
“…The more commonly encountered neoplasms in these 2 species include epithelial papilloma, androgen‐dependent atypical fibroma, mammary gland adenoma, and plasmactyoma . Atypical fibroma (and its malignant variant, atypical fibrosarcoma) has rarely been reported in hamsters and, to the best of the authors' knowledge, has never been reported in a Roborovski hamster.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ivermectin appeared to be very effective in the treatment of demodicosis in humans after only a single systemic dose of 200 μg/kg (combined with topical permethrin; the route of administration of ivermectin was not reported) 27 or oral 250 μg/kg alone 28 . Ivermectin has been reported to be an effective treatment of demodicosis in other species (dogs, 5,29 a koala 15 and hamsters 30 ). In this report, ivermectin was used at 600 μg/kg once daily.…”
Section: Discussionmentioning
confidence: 97%
“…Even under an immunosuppressive condition, the number of Demodex mites does not increase in humans [2]. In contrast, generalized demodicosis is frequently detected in dogs [18] and hamsters [19], indicating the relationship with immunodeficiency.Genetically immunodeficient mice have been used as a xenograft model as they fail to reject skin grafts. The absence of a functioning immune system allows xenogenic transplantation into severe combined immunodeficiency (SCID) mice without major graft rejection.…”
mentioning
confidence: 99%
“…Even under an immunosuppressive condition, the number of Demodex mites does not increase in humans [2]. In contrast, generalized demodicosis is frequently detected in dogs [18] and hamsters [19], indicating the relationship with immunodeficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation